KESALAHAN GRAMATIKA BAHASA ARAB PADA TULISAN MAHASISWA PRODI SASTRA ARAB UGM - Moh. Masrukhi (Arabic Literature Department, 2017)
Error in the language occurs due to speakers or learners already have rules of grammar different from other grammars being studied. An impact arises on the imperfection or inability of speakers implying the use of the language. This article will reveal the errors that arise as a result of the lack of dominance of the rules of the language being studied. The goal is to find out on what level the error occurred. This research data is taken from the final examination of the subjects of Arabic Text Review Semester I and Semester III students of Arabic. Further data is analyzed by utilizing existing Arabic structure concept or theory. The result is that these learners' language errors occur both on the lexicon, Arabic phrase and as well in Arabic clauses. From the results of this study can be argued that to avoid language errors, grammatical mastery or grammar of a second language requires a lot of practice, both written and oral.